Left atrial function in patients with heart failure with mid-range and preserved ejection fraction. (4th February 2022) - Stevanovic, A; Stankovic, I; Ilic Pasquali, N
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction Little is known about the left atrial (LA) function in patients with heart failure with mid-range and preserved ejection fraction (EF). We explored LA function in patients with heart failure with mid-range ejection fraction (HFmrEF) and compared to that in patients heart failure with preserved ejection fraction (HFpEF). Methods: A total of 66 HF patients (35 HFpEF and 31 HFmrEF) were included in the study. Left venticular EF, global longitudinal strain (GLS) and the mitral E/e" ratio were measured in all patients. LA function was assesed by measuring phasic changes in LA volume - maximal LA volume, pre-atrial contraction volume and minimal LA volume. All volumes were indexed to body surface area before calculating the indices of LA function: LA total emtying fraction (reservoir function), LA passive emptying fraction (conduit function) and LA active emptying fraction (pump function). Peak LA strain during ventricular systole (S-LAs) and peak LA strain during atrial systole (S-LAa) were measured also as LA functional parameters (reservoir and pump function). Conduit function of LA was derived as difference of S-LAs and S-LAa. LA deformation was also assessed by strain rate at different phases of the cardiac cycle. Strain rate analysis was used to measure peak LA strain rate during ventricular systole (SR-LAs), during early LV filling (SR-LAe) and during atrial contraction (SR-LAa). Results: There were no significant differences in GLS and the mitral E/e' between patients with HFmrEF and HFpEF (p > 0.05 for all). Significantly lower values of LA total emptyng fraction (47.6 ± 13.0 vs 38.9 ± 11.8, p = 0.006), LA passive emptyng fraction (26.6 ± 13, 2 vs 20.9 ± 9.4, p = 0.049) and LA active emptyng fraction (33.0 ± 10.0 vs. 26.0 ± 9.7, p = 0.005) were observed in HFmrEF tham HFpEF patients, respectively. Significantly lower values of S-LAs (27, 3 ± 5, 8 vs 22, 3 ± 8, 0, p = 0, 004), S-LAa (12, 8 ± 4, 0 vs 10, 3 ± 3, 7, p = 0, 01) (Figure 1), SR-LAs (1, 40 ± 0, 42 vs 1, 18 ± 0, 43, p = 0, 045), SR-Lae (-1, 47 ± 0, 56 vs -1, 13 ± 0, 51, p = 0, 012) and SR-LAa (-1, 90 ± 0, 50 vs -1, 64 ± 0, 55, p = 0, 044) were obtained in group of HFmrEF patients. Conclusions: All components of left atrial function were worse in patients with HFmrEF than in those with HFpEF, despite similar GLS and mitral E/e" ratio. Clinical and prognostic implications of these observations warrant futher research.